Investigation of Size-dependent Nonlinearity of Ag Nano-Fluids using Self-defocusing Technique - Al-Ani, Sally A.; Elias, Mazin M. (Iraqi Journal of Laser, 2019)
In this work, the effect of different particle size on the nonlinear optical properties of silver nanoparticles in de-ionized water was studied. The experimental observation of the far field diffraction patterns by CCD camera in two and three dimensions. The maximum change of nonlinear refractive index and the relative phase shift were calculated. The self-defocusing technique was used with a continuous-wave radiation from DPSS Blue laser .The wavelength is 473 nm with an output power of 270 mW. All the Ag colloids samples containing the sizes 15, 30, 50, and 70 nm of silver nanoparticles used in the study were chemically prepared. It was found that the nonlinear refractive index is a particle size dependent and of the order of 10-7 cm2/W, while its maximum change is in the order of 10-4. The phase shift increased from 8π up to 14π with particle size increment. The increase in the particle size of the Ag nanoparticles leads to increasing the number of rings and to the material possessing more nonlinearity with the nonlinear refractive index increment.